New Normal and Islamic Education: Islamic Religious Education Strategy On Educational Institutions in Indonesia - Amrin Amrin; Siti Asiah; M. Munawwir Al-Qosimi; Ade Irma Imamah; Mustika Utin Rochmawati; Nailis Shofita (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This study aims to find out how Strategy Islamic education in educational institutions in Indonesia in the new norm era.This study uses a qualitative approach with field research in State Junior High School 1 Ambalawi, Bima Regency, West Nusa Tenggara. As for the process of data collection techniques using observation, interview and documentation with data analysis using qualitative descriptive analysis. The results of the study indicate that the strategy of Islamic education teachers in the new normal era is carried out in accordance with the current situation this is a learning collaborate between face-to-face learning directly (offline) or indirectly (online), and sometimes carry out overall learning offline while staying on applicable health protocols. The process of implementing the strategy of Islamic education teachers in learning in the new normal era, namely by using the package books provided by the school while the learning videos are provided directly by the teacher. Supporting factors for learning strategies in the new normal era at State Junior High School 1 Ambalawi are support from several related parties, assistance internet quota, freedom to work and follow learning, teacher readiness in dealing with existing problems. Meanwhile, the obstacles faced by Islamic education teachers in implementing learning strategies are: in the new normal era at State Junior High School 1 Ambalawi as follows: a) lack of student involvement, 2) students' unequal access to media and, 3) time-limited learning, 4) perception mistakes from parents, 5) lack of internet quota assistance, 6) decreased student enthusiasm, 7) communication media constraints. Thus the teacher is expected to be able to provide and develop more varied learning methods in the use of learning directly or through Go online by developing the use of online and offline learning instruments easier to evaluate learners